2014 IEEE/RSJ International Conference on Intelligent Robots and Systems 2014
DOI: 10.1109/iros.2014.6942725
|View full text |Cite
|
Sign up to set email alerts
|

Toward automated intraocular laser surgery using a handheld micromanipulator

Abstract: This paper presents a technique for automated intraocular laser surgery using a handheld micromanipulator known as Micron. The novel handheld manipulator enables the automated scanning of a laser probe within a cylinder of 4 mm long and 4 mm in diameter. For the automation, the surface of the retina is reconstructed using a stereomicroscope, and then preplanned targets are placed on the surface. The laser probe is precisely located on the target via visual servoing of the aiming beam, while maintaining a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The image Jacobian update also improves the control performance by allowing the increment of gains used for visual servoing. As a result, it is found that the hybrid control approach improves the accuracy of robot-aided operation, compared to the position-based visual servo control [7]; the average error is reduced by 26.2%. The visual cues designed to maintain hand-eye coordination were useful in robot-aided operation, allowing repeatable experiments in both in the open-sky and eye phantom tasks, alleviating the limitations of previous work [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The image Jacobian update also improves the control performance by allowing the increment of gains used for visual servoing. As a result, it is found that the hybrid control approach improves the accuracy of robot-aided operation, compared to the position-based visual servo control [7]; the average error is reduced by 26.2%. The visual cues designed to maintain hand-eye coordination were useful in robot-aided operation, allowing repeatable experiments in both in the open-sky and eye phantom tasks, alleviating the limitations of previous work [7].…”
Section: Discussionmentioning
confidence: 99%
“…The first step is to register the CCD cameras with the Micron control coordinates (called herein the “ASAP coordinates”) by sweeping the tool above the retinal surface as described in [7]. Given multiple correspondences between 2D and 3D tip positions, projection matrices are obtained for the left and right cameras M c as in (1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to calibrate the tool tip offset, we use an approach developed in [14]. An optimizer is used to minimize the error between the projected and detected tip positions in both the cameras, while scanning the tool over the surface.…”
Section: Methodsmentioning
confidence: 99%